405nm laser processing of thin SU-8 polymer film - Cheong, Y.K.; Lim, W.H.; Lee, S.H.; Pua, C.H.; Chong, W.Y.; Ahmad, Harith (Elsevier, 2016)
This paper presents a comprehensive study on the effect of laser fluence on a negative tone thin film resist, SU-8, using an all-fibre 405 nm laser direct writing technique. 405 nm Gaussian beam is delivered on the spin-coated SU-8 thin film using single mode fibre, followed by subsequent chemical developing process. Disc structure is formed where its dimension is affected by the laser fluence. We found that polymer processing using this technique can be categorized into three stages. In the first stage (fluence > 90 J/cm2), lens shaped structure is formed with linear increase in diameter with logarithmic increase in laser fluence. In second stage (fluence > 600 J/cm2), flat-top disc structure is formed and the increase in disc diameter slows down with increasing laser fluence. In the third stage (fluence > 49 kJ/cm2), crater is formed at the centre of the disc due to laser ablation. Moreover, relatively large exposure fluence above the value required for complete polymerization has allowed collateral thermal-polymerization of the surrounding of the disc structure and reduced aspect ratio of the structure. Hence, by controlling laser writing fluence, different structures mentioned above can be produced. This understanding serves as a basis for polymer patterning using the proposed all-fibre laser direct writing technique, which finds potential application in micro-lens array, polymer optical waveguide, photomask and Lab-On-Chip fabrication.